Propagation of rhinacanthusnasutus (l.) Kurz., through encapsulated shoot tips and nodal segments for germplasm exchange and distribution - R. ELANGOMATHAVAN,; S. HARIHARAN,; P. KALAIVANAN,; S. NANCY BEAULAH, (International Journal of Pharma and Bio Sciences, 2017)
An encapsulation protocol to obtain synthetic seed was standardized in Rhinacanthus nasutus. In vitro grown shoot tips and nodal segments were encapsulated at different concentration of sodium alginate (2-5 % w/v) and calcium chloride (25 to 200 mM) was used as a gelling agent. Synthetic seeds were stored at 4 °C for a period of 6 months and re-growth frequency were assessed at different strength of MS medium (Full strength, half strength and quarter strength).The maximum response of in vitro grown encapsulated shoot tips was found to be the highest percentage of multiple shoot re-growth, when compared to nodal segments in the case of production of multiple shoot re-growth. Maximum shooting re-growth response (95%) of encapsulated shoot tips produced multiple shoots (6.0 ± 1.8) re-growth was observed on Murashige and Skoog (MS) medium supplemented with 6- Benzylaminopurine BAP (2.0 mg/l) and nodal segments re-growth response (85%) was observed with of multiple shoots (3.5 ± 0.5) cultured on MS medium with BAP (2.0 mg/l). The healthy shoots retrieved from the encapsulated shoot tips and nodal segments were rooted on half-strength MS medium augmented with Indole-3-butyric acid IBA (0.5 mg/l).